DAMPAK PERNIKAHAN USIA DINI PADA KESEHATAN REPRODUKSI - Peny Ariani; Gf Gustina Siregar; Purti Ayu Yessy Ariescha; Andayani Boang Manalu; Eka Sri Wahyuni; Monika Nina Ginting (INSTITUT KESEHATAN DELI HUSADA, 2021)
Marriage is a physical and spiritual bond in the form of a union between a man and a woman based on the desire to have offspring and a family. Basically, marriage is carried out by someone who has matured physically, psychologically and economically. However, in Indonesia, around 12-20% can still be found marriages that have not been accompanied by readiness from various aspects such as physical, economic, and knowledge of household life. This article uses qualitative and descriptive research methods that will explore more about early marriage and its relation to reproductive health. Early marriage is carried out by someone who is under 19 years old on average who is not ready for various aspects of marriage. This is likely to have an impact on reproductive health for both women and men. Therefore, various aspects of preparation are needed in carrying out the marriage so that efforts to avoid the negative impact of early marriage on reproductive health can be minimized